The breastfeeding effect on the tear film of women: an observational study - Alanazi, Mana Alafri; El-Hiti, Gamal Abdel-Rahman; Alshamrani, Amjad Ali; Baashen, Mashaaer Abdulwahhab; Fagehi, Raied; Masmali, Ali Mohammed (Journal of the Pakistan Medical Association, 2023)
Objective: To assess the tear film parameters in breastfeeding women. Method: The observational study was conducted at the College of Applied Medical Sciences, Riyadh, Saudi Arabia, from December 15, 2021, to February 12, 2022, and comprised healthy women aged 18-40 years who had no ocular diseases. Breastfeeding women were in group A and non-breastfeeding women formed the control group B. Ocular surface disease index, phenol red thread, and tear ferning tests were used in that order to assess the tear film for all the subjects. A gap of 5 minutes was allowed between phenol red thread and tear ferning tests. Data was analysed using SPSS, version 22. Results: Of the 50 subjects, 25(50%) were in group A with mean age 30.4 ± 5.9 years having a mean breastfeeding period of 5.4±5.0 months. The remaining 25(50%) women were in group B with mean age 28.5±2.1 years. Significant differences were found between the groups for ocular surface disease index, phenol red thread, and tear ferning (p<0.05). Significant moderate correlation was found between tear ferning grades and breastfeeding duration (p<0.05). Conclusion: Breastfeeding was found to increase dry eye symptoms in women. Key Words: Dry eye, Tear film, Tear ferning test, Breastfeeding, Risk factor.